216 ARRHYTHMOGENIC CARDIOMYOPATHY: IS THERE EVIDENCE OF AN INFLAMMATORY MYOCARDIAL DISEASE?. (15th December 2022) - De Gaspari, Monica; Rizzo, Stefania; Carturan, Elisa; Marra, Martina Perazzolo; Corrado, Domenico; Bauce, Barbara; Pilichou, Kalliopi; Thiene, Gaetano; Basso, Cristina
Abstract: Background and aim: Arrhythmogenic cardiomyopathy (ACM) is a heredo-familiar primary heart muscle disease, mainly due to mutations of desmosomal genes and characterized by progressive myocardial atrophy with fibro-fatty replacement, causing electrical instability at risk of sudden cardiac death (SCD). Since the first anatomopathological descriptions, the hypothesis that myocardial inflammation could have an important role in the onset and evolution of ACM has been advanced. With this work we aim to describe the prevalence of inflammatory cells in ACM and their characterization through histological and immunohistochemical (IHC) analysis in endomyocardial biopsy (EMB) and heart specimens coming from either SCD or heart transplantation (HTx). Material and methods: We analysed EMB and whole heart specimens (from juvenile SCD registry – below 40 years of age at the time of death – and HTx) with a diagnosis of ACM, focusing on the presence of inflammatory infiltrates. For the whole hearts, in a subgroup of cases the inflammatory infiltrate was evaluated on 9 myocardial sections by applying a semi-quantitative score according to the number of sections involved (0 = none; 1 = 1 section involved; 2 = 2-5 sections; 3 = >5 sections) and an IHC panel for myocarditis on 1 right ventricular and 1 left ventricular section (CD45, CD3, CD8, CD4, CD68, CD20, CD138 and vimentin- as a control for fibroblast). Results: Among the 63 analysed EMB (41 M, mean age 45 years, range 18-71 years), 26 cases (41%) showed foci of inflammation with CD3+ > 7/mm 2 . In all cases viral genome (DNA and RNA virus) was absent. A total of 106 heart specimens with a diagnosis of ACM were enrolled, including 73 juvenile SCD (49 M, mean age 26 years) and 33 HTx (18 M, mean age 45 years). Inflammation was reported in 95% of SCD an d 67% of HTx. The inflammatory infiltrate was focal or multifocal in all, except one case of juvenile SCD with diffuse myocarditis in the postero-lateral wall of the left ventricle. In the 24 reviewed cases, the inflammation was focal with a mean inflammatory score of 1.75 ±0.9 in the HTx group and 1.5±0.9 in the SD group (p = NS). By IHC we showed that: a) there is no significant difference in the inflammatory score between SD and HTx; b) the inflammation is mostly near-scarring (13 cases); c) inflammatory cells consist prevalently of cytotoxic T lymphocytes CD3+CD8+ (with CD4+<CD8+ both in SD and HTx, p < 0.05). Conclusions: Our pathological data confirm that ACM is an inflammatory cardiomyopathy with a higher prevalence of inflammation in SCD cases. The inflammatory infiltrate is mainly composed of cytotoxic T lymphocytes with a variable presence of macrophages. These data, combined with the recent experimental studies demonstrating the role of immune mediators in the evolution of the disease, support the potential application of immunosuppressive therapy in ACM.